PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 060830 MEDAN PETISAH - Martalena Daeli; Juliana; Riski Bastanta B. Manalu; Antonius Remigius Abi; Anton Sitepu; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the project-based learning (pjbl) learning model on student learning outcomes in the Science and Social Education subject class IV SD Negeri 060830 Medan Petisah Academic Year 2024/2025. The research method used is an experimental method with a quantitative research type. To obtain data in this study, 26 questions were used as many test instruments. The number of research samples was 26 students based on the saturated sampling technique. The results of this study show that before being given pretest, students have an average learning outcome of 41.26 which is included in the poor category. After being given treatment, the results of the (posttest) had an increase with an average score of student learning outcomes of 79.84 by achieving a good category score. It can be said that the success rate of student learning outcomes has increased, as evidenced by the results of the correlation coefficient test calculation obtained r_count ≥ r_tabel with a result of 0.611 ≥ 0.388. Next, hypothesis testing that compares the t_count ≥ t_table . The obtained value of t_count = 3,780 while t_table =1,706. Because t_count ≥ t_table (3,780 ≥ 1,706 then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive between the type PjBL Learning model (X) on student learning outcomes (Y).